2016
DOI: 10.3945/ajcn.116.140954
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein intake and risk of type 2 diabetes: results from the Melbourne Collaborative Cohort Study and a meta-analysis of prospective studies

Abstract: Background: Reported associations between protein intake from different sources and type 2 diabetes (T2D) have been inconsistent. Objective: We prospectively examined the relations of total, animal, and plant protein intakes with incident T2D. Design: We followed 21,523 participants (women: 61.7%) between 1990 and 2007 from the Melbourne Collaborative Cohort Study who were free of diabetes, cardiovascular disease, cancer, and kidney stones at baseline. We also conducted a meta-analysis that included the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
98
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 36 publications
8
98
3
4
Order By: Relevance
“…The PP diets were shown to reduce the incidence of T2DM and cardiovascular disease, while AP diets increased such incidences. [5][6][7][8]38 Unexpectedly, the present data showed a similar improvement in glycaemic and metabolic control in both dietary groups. Although the metabolic improvement might have been attributable to the dietary intervention and moderate weight loss per se, the absence of major differences between the AP and PP groups indicates that the protein composition did not affect the response to the intervention.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The PP diets were shown to reduce the incidence of T2DM and cardiovascular disease, while AP diets increased such incidences. [5][6][7][8]38 Unexpectedly, the present data showed a similar improvement in glycaemic and metabolic control in both dietary groups. Although the metabolic improvement might have been attributable to the dietary intervention and moderate weight loss per se, the absence of major differences between the AP and PP groups indicates that the protein composition did not affect the response to the intervention.…”
Section: Discussionsupporting
confidence: 81%
“…The PP diets were shown to reduce the incidence of T2DM and cardiovascular disease, while AP diets increased such incidences . Unexpectedly, the present data showed a similar improvement in glycaemic and metabolic control in both dietary groups.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the last few years many studies started to questioning the effects of animal (e.g., meat and dairy products) and plant (e.g., grains and legumes) proteins intake on risk to develop cardiovascular disease and cancer [112,113]. In a recent meta-analysis proteins intake from plants is associated with a decrease risk of diabetes, whereas animal proteins with an increase of it [114,115].…”
Section: High Protein Diet In Nafld Cure or Disease?mentioning
confidence: 99%
“…The present study also confirmed that higher intakes of total protein, animal protein, animal fat and SFA were only significantly associated with the development of diabetes mellitus in the obese group. Similarly, total protein and animal protein intake are risk factors for the development of diabetes mellitus, based on the findings of European and American studies, as well as a meta‐analysis. It is possible that amino acids reduce the endocrine function of the pancreas, act as gluconeogenic precursors in the liver and increase insulin resistance through the hexosamine biosynthetic pathway.…”
mentioning
confidence: 99%